Atypical Antipsychotics: Sleep, Sedation, and Efficacy - Miller, Del D. (Physicians Postgraduate Press, Inc., 2004)
Patients with schizophrenia often suffer from sleep disturbances such as excessive sleeping and insomnia. Common medications for schizophrenia can have a sedative effect on patients. Not all antipsychotic medications have the same sedative effect, which is related to dosage and affinity for histamine H(1) receptors. Studies have shown that, compared with conventional antipsychotics, atypical antipsychotics such as risperidone, olanzapine, quetiapine, and ziprasidone generally cause less sedation yet are as effective in controlling psychosis and agitation. Sedation can be troublesome to patients who are trying to become reintegrated into society and interfere with their treatment regimen. Both persistent sedation and chronic insomnia can be managed by the physician.